Anchored strategic reasoning - Radosveta Ivanova-Stenzel; Gyula Seres (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
Anchoring is a robust behavioral phenomenon modeled predominantly as a bias in individual judgment. We propose a game-theoretic model that considers players' beliefs about others' behavior as a mediator for the effect of the anchor on a player's choice. The results establish that anchoring in strategic interactions reported in the literature can be rationalized by anchored beliefs about the opponents' intentions. Notwithstanding, we also demonstrate that a player might adjust away from rather than toward the anchor in games where choices are strategic substitutes.
Keywords: D01; D91; C72; 330; Anchoring Bias; Auctions; Games; Incomplete Information; Strategy